Does the healthcare system know what to cut under the pandemic emergency pressure? An observational study on geographic variation of surgical procedures in Italy - Milena Vainieri; Sabina Nuti; Domenico Mantoan (BMJ Open, 2022)
Objectives During 2020 many countries reduced the number of elective surgeries to free up beds and cope with the COVID-19 outbreak. This situation led healthcare systems to prioritise elective interventions and reduce the overall volumes of treatments.The aim of this paper is to analyse whether the pandemic and the prioritisation policies on elective surgery were done considering the potential inappropriateness highlighted by the measurement of geographic variation.Setting The setting of the study is acute care with a focus on elective surgical procedures. Data were analysed at the Italian regional level.Participants The study is observational and relies on national hospitalisation records from 2019 to 2020. The analyses refer to the 21 Italian regional health systems, using 48 917 records for 2019 and 33 821 for 2020. The surgical procedures analysed are those considered at high risk of unwarranted variation: coronary angioplasty, cholecystectomy, colectomy, knee replacement, hysterectomy, tonsillectomy, hip replacement and vein stripping.Primary and secondary outcome measures Primary measures were the hospitalisation rate and its reduction per procedure, to understand the level of potential inappropriateness. Secondary measures were the SD and high/low ratio, to map the level of geographic variation.Results For some procedures, there is a linear negative relationship (eg, tonsillectomy: ρ = −0.92, p<0.01; vein stripping: ρ = −0.93, p<0.01) between the reduction in hospitalisation and its starting point. The only two procedures for which no significant differences were registered are cholecystectomy (ρ = −0.22, p=0.31) and hysterectomy (ρ = −0.22, p=0.33). In particular, in all cases, data show that regions with higher 2019 hospitalisation rates registered a larger reduction.Conclusions The Italian data show that the pandemic seems to have led hospital managers and health professionals to cut surgical interventions more likely to be inappropriate. Hence, these findings can inform and guide the healthcare system to manage unwarranted variation when coming back to the new normal. This new starting point (lower volumes in some selected elective surgical procedures) should be used to plan elective surgical treatments that can be cancelled because of their high risk of inappropriateness.